Mempraktikkan Pembelajaran yang Bernuansa Paikemi - Baidah Baidah; Damilsi Hijaya; Ummul Rahmah; Nur Salwa Harahap; Gusmaneli Gusmaneli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The PAIKEMI approach in PAI learning allows students to experience a meaningful learning transformation and have a positive impact. This strategy allows students to relate Islamic teachings to their daily life experiences, increase holistic understanding, awaken creativity, connect Islamic values with practical actions, and improve critical and analytical thinking skills. It is hoped that implementing PAI learning strategies using the PAIKEMI approach can help students not only gain knowledge, but also be able to apply Islamic values in their daily lives in a more effective and meaningful way.